2014
DOI: 10.1021/am500845x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Mechanical Properties, and in Vitro Biocompatibility with Osteoblasts of Calcium Silicate–Reduced Graphene Oxide Composites

Abstract: Calcium silicate (CaSiO3, CS) ceramics are promising bioactive materials for bone tissue engineering, particularly for bone repair. However, the low toughness of CS limits its application in load-bearing conditions. Recent findings indicating the promising biocompatibility of graphene imply that graphene can be used as an additive to improve the mechanical properties of composites. Here, we report a simple method for the synthesis of calcium silicate/reduced graphene oxide (CS/rGO) composites using a hydrother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(110 citation statements)
references
References 80 publications
3
106
1
Order By: Relevance
“…These results show good consistency with those of ARS and von Kossa staining, other markers for late osteogenic differentiation. These results are supported by recent evidence showing that rGO/ calcium silicate and GO/calcium phosphate composites have a synergistic effect in accelerating the osteogenesis of osteoblasts and MSCs by significantly increasing calcium deposition [67,68], underscoring the need for such hybrid composites for bone tissue engineering. Moreover, it has been revealed that gelatinfunctionalized GO can be efficiently used for the biomimetic mineralization of HAp, leading to promote the osteogenic differentiation of MC3T3-E1 cells [61].…”
Section: Effects Of Rgo/hap Composites On Expression Of Osteogenic Prsupporting
confidence: 72%
“…These results show good consistency with those of ARS and von Kossa staining, other markers for late osteogenic differentiation. These results are supported by recent evidence showing that rGO/ calcium silicate and GO/calcium phosphate composites have a synergistic effect in accelerating the osteogenesis of osteoblasts and MSCs by significantly increasing calcium deposition [67,68], underscoring the need for such hybrid composites for bone tissue engineering. Moreover, it has been revealed that gelatinfunctionalized GO can be efficiently used for the biomimetic mineralization of HAp, leading to promote the osteogenic differentiation of MC3T3-E1 cells [61].…”
Section: Effects Of Rgo/hap Composites On Expression Of Osteogenic Prsupporting
confidence: 72%
“…Note that different observations among the apatite layer growth on the surface of samples are relevant to their morphologies which are also in agreement with the observations made by several research groups [33,34].The results showed that the apatite morphology varied among bioceramics. This morphological difference was attributed to changes in the ion concentrations and pH in SBF after the soaking of different bioceramics [35]. Moreover, EDS spectra shown in Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…A simplified Hummers' method was used to synthesize graphene oxide (GO) (Mehrali et al 2013a(Mehrali et al , 2014a and the NDG was prepared by a hydrothermal process with GO as raw material in an ammonia solution. As shown in Fig.…”
Section: Synthesize Of Nitrogen-doped Graphenementioning
confidence: 99%